Morphometry Of Neck-Shaft Angle And Neck Length Of Femur And It’s Correlations: A Cross Sectional Study - Chawla, Shivani; Aneja, Prachi Saffar; Saha, Susmita; Kumar, Bhavesh; Sharma, Yamini; Yadav, Ruchika (Journal of Neonatal Surgery, 2025)
BACKGROUND: Total hip replacement is a very common procedure nowadays. The hip joint is under constant tension as it carries the weight of the upper body. Osteoarthritis does not cause any damage to the hip joint. Designing a prosthesis for a specific ethnic group requires consideration of the femoral neck-shaft angle, neck length geometry, etc. AIM & OBJECTIVES: Study was aimed to estimate parameters of neck-shaft angle and neck length of right and left femur and correlate the above parameters among them. MATERIALS AND METHOD: Present study was a descriptive cross sectional study on 50 Dry femurs (25 right and 25 left) which were randomly obtained from the bone bank of Department of Anatomy, FMHS, SGT University. Dry, undamaged, and non-pathological femurs were included in the study; femurs with tumours, fractures, trauma, or any other pathological abnormalities were excluded. Measurements were taken using anthropometric tools such as a goniometer, digital Verneircalliper, and osteometric board. RESULTS: To compare the morphometric parameters in accordance of right and left femur, student ‘t’ test was performed and it was found that comparison of all parameters of both side femur bones was not statistically significant. Second objective of this study, observed that femur length is not significantly correlated with Femur Neck Length and Neck-Shaft Angle. CONCLUSION: These parameters can be used inaccuracy and success of the hip replacement surgery demands complete knowledge of the neck shaft angle. The values obtained were greater in western world than in present study. So, the regional variations were found among different regions of world. This study will applaud biomechanical engineers to manufacture and build the implants with accurate morphometric data to suit Indian population and for enhance surgical consequences with prevention of complications.